KEPUASAN SEBAGAI MEDIASI PENGARUH SERVICE QUALITY DAN CUSTOMER INTIMACY TERADAP LOYALITAS NASABAH - Yeyen Novita; Ari Setiawan; Ahmad Ulil Albab Al Umar (Program Studi Ekonomi Islam, Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2021)
This study observes the influence of Service Quality and Customer Intimacy on Customer Loyalty at Bank Muamalat KC Solo with Satisfaction as an Intervening variable. This study applies quantitative methods with a total of 100 respondents. The result was analyzed through statistical tests, classical assumption tests and path analysis on SPSS version 23. The finding shows: Service Quality has a significant positive effect on customer loyalty. Customer Intimacy has no significant positive effect on customer loyalty. Service Quality has a significant positive effect on satisfaction. Customer Intimacy has a significant positive effect on satisfaction. Satisfaction has a significant positive effect on customer loyalty. Satisfaction is not able to facilitate the effect of Service Quality and Customer Intimacy on Customer Loyalty. The implications of this research are expected as a reference in order to measure the extent to which the object of this research is in providing services to customers, and measuring how satisfied customers are.